PERKEMBANGAN KINERJA KEUANGAN PADA PT. ASTRA OTOPARTS TBK (TAHUN 2019- 2021) DENGAN MENGGUNAKAN ANALISIS COMMON SIZE - Titi Rahmawati; Hari Sulistiyo (Universitas Boyolali, 2022)
Financial statements are a means to determine the company’s financial performance in order to obtain valuable results. The aim is to analyze the development of the financial performance of PT. Astra Otoparts Tbk from year to year, based on the 2019 and 2021 balance sheets and income statements using the usual size analysis technique. Researchers used descriptive research methods with a quantitative approach used for research methods. Based on the survey results, in 2020 there will be a decline. This is due to an increase in liabilities that have an impact on equity. The difference between the asset’s carrying amount and its recoverable amount is reported as an impairment loss or percentage loss. According to the income statement, the company’s marketing strategy was ineffective as evidenced by the increase in cost of goods sold and a decrease in gross profit margin. In terms of the company’s ability to generate profit, its net profit margin decreased year over year to a loss in 2019-2021. This shows that the company’s financial strength is decreasing because profitability has to fall to a loss.